Peningkatan Motivasi Belajar Siswa dalam Pembelajaran IPS dengan Menggunakan Media Gambar pada Kelas III Di SDN Larangan Badung 1 Palengaan Pamekasan - Sunu, Sunu (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this research is to enhance student motivation in social studies learning by using visual media in the third grade at SDN Larangan Badung 1 Palengaan Pamekasan. This research is a Classroom Action Research (CAR) conducted in two cycles. The subjects of this study are the third-grade students of SDN Larangan Badung 1. Each cycle consists of 4 stages: planning, implementation, observation, and reflection. Data collection in this study uses observation, interviews, and documentation. The data obtained are analyzed qualitatively and quantitatively in a descriptive manner. The results of the research in cycle 1 during the first meeting showed an average percentage of student motivation to learn categorized as very low at 37.5%, and in the second meeting, the average percentage of student motivation to learn reached 57.5%. In cycle II, during the first meeting, the average student motivation to learn experienced an increase, although it still did not reach the success indicator of 75%, which falls under the sufficient category. In the second meeting, the average percentage of student motivation to learn increased, reaching 85% in the very good category